1969
DOI: 10.1111/j.1469-8986.1969.tb02896.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stimulus Order and Novelty on Orienting Responses

Abstract: The effects of stimulus order and novelty upon habituation and dishabituation of the GSR component of the OR were investigated. The numbers 21 to 60 were presented in serial order (Ordered-Novel group), and in random order (Random-Novel group), and the number 21 was repeated 40 times (Similar group). The number 600 was occasionally interpolated among each series. No group differences in magnitude of OR to the first stimulus or in habituation of the OR during the series of numbers were found. Dishabituation due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
1

Year Published

1970
1970
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 10 publications
1
20
1
Order By: Relevance
“…Ancillary predictions based on Sokolov's description of the OR, however, lead to the expectation that dishabituation of the OR to subsequen t in·series stimuli would occur as a function of the amount of disparity present in the test trial. Although this fmding was reported by Zimny & Schwabe (1965) for tonal stimuli, it was not clearly present in this study or in Zimny, Pawlick, & Saur's (1969) report.…”
Section: Svbjects and Apparatvscontrasting
confidence: 55%
See 1 more Smart Citation
“…Ancillary predictions based on Sokolov's description of the OR, however, lead to the expectation that dishabituation of the OR to subsequen t in·series stimuli would occur as a function of the amount of disparity present in the test trial. Although this fmding was reported by Zimny & Schwabe (1965) for tonal stimuli, it was not clearly present in this study or in Zimny, Pawlick, & Saur's (1969) report.…”
Section: Svbjects and Apparatvscontrasting
confidence: 55%
“…Basically, though, these fmdings confmn and extend those of Vnger (1964) and Zimny et al (1969) and certainly indicate that at least some of the parameters of the OR transcend the level of simple physical stimuli. In this respect the present study also suggests that OR and related research involving novelty manipulations in semantic, verbal, and other conceptual dimensions might profit from rigorous investigations of quantitative and directional changes in the stimulus.…”
Section: Svbjects and Apparatvsmentioning
confidence: 99%
“…Beyond that, due to presentations of various stimuli, a slight weakening of the selectivity of the habituation process, i.e., habituation generalisation, might be expected to occur both in the random and in the regularity group. With respect to the size or rate of response habituation, no clear prediction can be derived from the literature (cf., e.g., Zimny et al, 1969). While it might be expected from Sokolov's OR theory (1963) that the rate of habituation would be greatest for a series of identical stimuli, next greatest for stimuli presented in serial order and slowest for stimuli presented in random order, Zimny et al (1969) actually found no differential effects of these three conditions on the amount of SCR habituation.…”
Section: Introductionmentioning
confidence: 74%
“…With respect to the size or rate of response habituation, no clear prediction can be derived from the literature (cf., e.g., Zimny et al, 1969). While it might be expected from Sokolov's OR theory (1963) that the rate of habituation would be greatest for a series of identical stimuli, next greatest for stimuli presented in serial order and slowest for stimuli presented in random order, Zimny et al (1969) actually found no differential effects of these three conditions on the amount of SCR habituation. Ex post it is a bold venture to reconcile these findings with the predictions derived from the theory, even if habituation should eventually relate to the elaboration of a forecast about the most probable sequence of future events only.…”
Section: Introductionmentioning
confidence: 74%
“…Several studies have tried to clarify the habituation pattern in such sequences (e.g., Furedy, 1968;Zimny, Pawlick, & Saur, 1969). Frith (1978a, 1978b) have raised the possibility that different laws may govern the habituation process in complex and simple sequences of stimuli.…”
mentioning
confidence: 99%